Evaluation Of Facilities And Infrastructure Of The Building Information Modeling Design Department (DPIB) at SMK N 1 Lintau Buo Based On Permendikbud No 34 of 2018 (Jurnal Vokasi Mekanika, 2025)
Vocational High Schools face several issues related to the facilities and infrastructure of the practical room for the Building Modeling and Information Design Expertise Program (DPIB), such as a lack of adequate drawing tables and uncomfortable, hot room conditions, which reduce student comfort. Additionally, supporting equipment such as cleaning tools and safety equipment (K3) are insufficient, and the maintenance of facilities is not carried out optimally. These conditions hinder the effectiveness of the learning process and do not meet the national standards set by Permendikbud Number 34 of 2018.This study aims to evaluate the adequacy of facilities and infrastructure in the practical room of the Building Modeling and Information Design Expertise Program (DPIB) at SMK Negeri 1 Lintau Buo, based on the standards outlined in Permendikbud Number 34 of 2018. The evaluation focuses on equipment completeness, the physical condition of the practice room, and other supporting facilities used for learning activities. The research employs an evaluative method with a quantitative descriptive approach. Data were collected through direct observation, interviews with school officials, and documentation of the existing facilities.The results indicate deficiencies in the quality of the drawing tables and the uncomfortable condition of the practice room, both of which could potentially hinder the achievement of national education standards. This research is expected to provide valuable input for the school to improve its facilities and infrastructure to support more effective and efficient learning activities in the future.